Influence of aluminum alloys surface treatment on the durability of glued joints - Kowalik, Joanna; Tworek, Magdalena; Smaruj, Michał (Polimery, 2023)
The aim of the work was to analyze the method of preparing the aluminum surface in terms of the functional properties of glued joints with the use of one-component polyurethane adhesive. Six methods of surface treatment of EN AW-5251 aluminum alloy were tested. In addition, changes in the shear strength of adhesive joints after environmental exposure were determined. The best surface preparation processes were atmospheric plasma and anodizing.